Effect of micro-defects on structure failure: Coupling asymptotic analysis and strong discontinuity - Noël, Virginie Bonnaillie-; Brancherie, Delphine; Dambrine, Marc; Tordeux, Sébastien; Vial, Grégory (European Journal of Computational Mechanics, 2010)
This work aims at taking into account the influence of geometrical defects on the behavior till complete failure of structures. This is achieved without any fine description of the exact geometry of the perturbations. The proposed strategy is based on two approaches: asymptotic analysis of Navier equations and strong discontinuity approach.